Diagnosis and Management of Haemorrhagic Complications Following Hepatopancreatobiliary Surgery - Balakrishnan, Anitha; Rinkoff, Sirke; Goldsmith, Petra; Harper, Simon J F; Jamieson, Neville V; Huguet, Emmanuel L; Jah, Asif; Praseedom, Raaj K (JOP. Journal of the Pancreas, 2015)
Context Post-operative haemorrhage is a known complication of hepatopancreatobiliary surgery. Prompt treatment minimizes mortality and morbidity; however, there is currently little uniformity in the management of this complication. Objective The total numbers of pancreatectomies or liver resections were identified using hospital episode statistic data. Methods Patients who experienced post-operative bleeding were identified with keyword searches of all discharge letters, imaging reports and the theatre-coding database for the period between January 2005 and December 2011. Treatment modalities for control of haemorrhage as well as morbidity, mortality, length of stay and survival were examined. Results Thirty-four of the 768 pancreatic and liver resections performed experienced post-operative haemorrhage. More patients bled following pancreatectomies (6.1%) compared to hepatectomies (2.5%). Bleeding was controlled using endoscopic, interventional radiological or surgical methods; re-laparotomy provided definitive management in the majority of patients. Post-pancreatectomy haemorrhage was associated with significantly increased mortality (P=0.004). Length of stay was increased following haemorrhage post-pancreatectomy or hepatectomy (P<0.05). Conclusions Our study highlights the substantial increase in mortality and length of stay following post-pancreatectomy and post-hepatectomy haemorrhage. Re-laparotomy was frequently required for control of bleeding. Our proposed management algorithm based on the timing and site of bleeding may standardize treatment in this heterogeneous group. Image: Algorithm for the management of late post-resectional haemorrhage.